TECHNICAL PLANNING OF WASTE TREATMENT PLANT (REDUCE REUSE RECYCLE) SEDATI DISTRICT, SIDOARJO - Amiruddin Al Mahmudi; Yusrianti Yusrianti; Dyah Ratri N. (Konversi, 2022)
Population development is accompanied by an increase in the volume of waste that arises in an area. Sanitation problems are started by the amount of waste that cannot be handled. Sidoarjo Regency in 2018 had a population of 2,238,069 people with waste generation of 1119 tons/day. Waste processing plays an important role in the problem of waste in Sidoarjo Regency. The coastal part of Sedati District is Kalanganyar Village, Buncitan Village, Cemandi Village, Gisik Cemandi Village, Banjar Kemuning Village, Tambak Cemandi Village, and Segoro Village. In implementing the 3R TPS planning, data on waste generation, volume of waste generation and composition of waste generated by the community are needed every day. The calculation method used in this plan refers to SNI 19-3964-1994. From the data obtained, waste generation is 0.36 kg/person/day and waste volume is 132.93 kg/m3. And it is planned that the 3R TPS will operate for the next 10 years or in 2031. The planned waste management and processing at TPS 3R Sedati District is divided into 2, namely organic waste processed into compost and non-organic waste sold to collectors, and for residual waste that is not processed it is transported to landfill. The area of land required for planning TPS 3R is 1751.5 m2 which is located in Tambak Cemandi Village. The budget plan that must be issued for planning TPS 3R Sedati District is Rp. 3,180,875,000.00.